Sistem Informasi Penggajian Karyawan Pada PT.X Berbasis Web - Zaguar Rigil Saputro; Lily Puspa Dewi; Justinus Andjarwirawan (Jurnal Infra, 2017)
PT. X is a company who activein sales and service of factory instrument. The company as a supplier to other companies who need factory instrument. The factory Instrument sold by this company include control valves, liquid level meters, self operated regulators, and schuh technology. PT. X now has many customer from the entire of Indonesia especially in Java dan Kalimantan. Currently PT. X already has employee who grow along with te company’s growth.One of things who need to noticed with increasing  of employees is management in payroll section. This company still apply payroll system manually using Microsoft Office Excel. Payroll manually will hamper the effectiveness of time in manage employee salary.Based on the previous problem, one of solution that can be done is  making information system of employee’s payroll PT. X. This system made by programming language PHP and MySQL as database. This system is expected to increase the effectiveness of time in manage employee salary.